PENGARUH CASH HOLDING, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Wiyani Prameswari, Kristella Devina; Ratnaningsih, Stephana Dyah Ayu (FEB Universitas Sam Ratulangi Manado, 2023)
This research is motivated by the situation in the mining industry, where growth has temporarily decreased. Therefore, companies in this industry are expected to achieve maximum profits and meet the expectations of investors. The purpose of this study was to examine the effect of Cash Holding, Profitability, and Liquidity on Firm Value in Mining Companies during the 2018-2022 period. This type of research is quantitative research. The sample in this study was obtained using purposive sampling method which uses certain criteria in sampling. The analysis method used in this research is multiple linear regression analysis. The results of this study indicate that (1) Cash Holdings has a negative effect on firm value, the first hypothesis is accepted (2) Return on Assets has a positive effect on firm value, the second hypothesis is accepted, (3) Current Ratio has no effect on firm value, the third hypothesis is rejected. Overall, this research is important to evaluate the performance of a company in its operating activities in order to achieve maximum profit so as to increase the value of the company. So, further research should add other variables that affect firm value such as good corporate governance, company size or ownership structure.